How Do Virtual Influencers Affect Consumer Brand Evangelism in the Metaverse? The Effects of Virtual Influencers’ Marketing Efforts, Perceived Coolness, and Anthropomorphism - Maja Gulan; Yuanyue Feng; Gustave Florentin Nkoulou Mvondo; Ben Niu (Journal of Theoretical and Applied Electronic Commerce Research)
Modern commercial organizations have started to embrace the metaverse platform as a new channel for marketing their products and services. As prominent brand representatives, virtual influencers are responsible for strengthening consumer–brand connections in the metaverse. However, the ways in which virtual influencers contribute to consumers’ brand fidelity and evangelistic behaviors remain unknown. To address this gap, this work explores the essential factors that impact consumers’ intention to trust virtual influencers in the metaverse, purchase the products that they promote, and engage in brand evangelistic behaviors. Specifically, a new framework is developed that integrates metaverse virtual influencers’ marketing efforts, perceived coolness, anthropomorphism, brand evangelism, and brand fidelity into a comprehensive conceptual research model. Survey results obtained from 713 respondents in the US demonstrate that marketing efforts, perceived coolness, and anthropomorphism positively influence brand evangelism. The findings also indicate that consumers’ brand fidelity encourages brand evangelism and mediates the relationship between virtual influencers’ features, marketing efforts, and consumers’ brand evangelistic behavior. This study’s significance lies in its focus on the evolving marketing dynamics in the metaverse. It considers how virtual influencers’ features and marketing efforts impact consumers’ brand-related attitudes and behaviors in the metaverse, offering valuable insights for the advancement of metaverse marketing research and practice.